The relationship between upper-body and lower-body power with speed climbing performance in bandung city athletes: a correlational study - Devia Ariana Indrani; Alen Rismayadi; Geraldi Novian (IICET (Indonesian Institute for Counseling, Education and Therapy), 2026)
On a typical 15-meter-high wall with a 5° overhang, world-record-level speed climbing requires incredibly quick, explosive, and effective vertical motion. Biomechanical power components, especially upper-body and lower-body power, are important factors that determine athletic performance, as seen by the pattern of world records showing a considerable and constant decrease in time. However, there is still a dearth of research that particularly examines the connection between these two elements in athletes competing at the national level in speed climbing. The purpose of this study is to examine how speed climbing athletes in the world record category perform in relation to upper-body power, lower-body power, and their combination. All speed climbing athletes from the Bandung City FPTI (n=14, total sampling technique) were subjected to a quantitative approach using a correlational design. The medicine ball chest pass test was used to measure arm power, leg power utilizing the vertical jump test, and speed world record performance using the IFSC's automatic timing system with a standard resolution of 1/1000 of a second for the 15-meter course completion time. Using SPSS version 25, statistical analysis includes descriptive tests, the Shapiro-Wilk normality test, and Spearman's rho correlation test. Upper-body power was strongly and negatively associated with climbing time (rs = -.802, p = .017, approximate 95% CI [-.935, -.473]), and lower-body power showed a similar strong negative association (rs = -.814, p = .014, approximate 95% CI [-.939, -.497]). Upper- and lower-body power were also strongly positively associated (rs = .820, p < .05). These findings indicate that athletes with higher upper- and lower-body power tended to record faster climbing times. Because the study used a correlational design and a small sample, the results should be interpreted as associations rather than evidence of causality.